A study on school location determination and suitability using analytical hierarcy process (AHP) in geographical information system (GIS) approach / Abd. Manan Samad, Abdul Rahman Abdul Latif and Khairil Afendy Hashim - Samad, Abd. Manan; Abdul Latif, Abdul Rahman; Hashim, Khairil Afendy (Research Management Institute (RMI), 2013)
The proposed project is focuses on determination of school location for secondary school covering district of Perlis State. The Perlis State has seen an increase in population over the last twenty years. With the increased number of population, the time is right for a suitability study in order to determine the location for a new school in this state. The overall aim of this research study is to evaluate and propose the most suitable criteria for new school location determination by using GIS and other related approach. The specific objectives are i) to study the existing criteria for new school location determination at PPD (Pejabat Pendidikan Daerah)/MOE (Ministry of Education) level; ii) to revise and propose a new most suitable criteria for new school location determination, iii) develope, simulate and evaluate a proposed model of most suitable new school location with the implementation of the most suitable criteria by using GIS approach. It is expected that result/outcome from this research study will be able in helping PPD/MOE in preparing a comprehensive departmental paper work or proposal of new school establishment for submission to the Department of State Education (JPN) and Ministry of Education (MOE). Suggested or proposed method could reduce stages that involved in determining new school establishment (location determination) and other related useful information such as insufficient number of teachers by option, classes and distances between existing school and housing area.